Comprehensive strain analysis in oncological patients undergoing thoracic radiotherapy: 1-year follow-up of a prospective study comparing proton vs. photon beam therapy. (14th October 2021) - Cordova-Madera, S N; Garcia-Bello, L; Bruno, G; Di Stefano, C; Quintero-Martinez, J A; Laack, N; Corbin, K; Whitaker, T; Pellikka, P; Herrmann, J; Mutter, R; Villarraga, H R
Abstract: Background: Proton beam therapy (PBT) is a promising radiotherapeutic method by which the proton Bragg peak may be exploited to reduce the dose to non-target normal tissues, when compared with the conventional photon treatment (PhT). Purpose: To evaluate the mechanical function of the left ventricle by endocardial longitudinal (GLS-basic strain), circumferential (GCS) and radial strain (GRS) and systolic (SRs) and early diastolic (SRe) strain rate following thoracic radiotherapy. Methods: Between March 2016 and March 2017, 58 patients with breast or thoracic cancer scheduled to receive radiotherapy were enrolled prospectively and, underwent 2D-STE echocardiography with basic (GLS) and comprehensive (GCS, GRS, GLSRs, GCSRs, GRSRs, GLSRe, GCSRe, GRSRe parameters) analysis at pre-treatment, mid-treatment, end of treatment, 3 month and 1 year follow-up. LVEF was calculated by the biplane Simpson technique. Shapiro-Wilk's test was performed to evaluate the normal distribution of the data. Comparison between groups was performed with Student's t-test or Wilcoxon test for quantitative variables and with Chi-Square test or Fisher's exact test for qualitative variables. Tukey-Kramer method was used to compare means during follow up. A p-value <0.05 was assumed as the level of statistical significance. Results: Mean age was 53.3±10.9 years and 91.3% were women. PBT was used to treat 38 patients; PhT in 20. The median of the mean heart dose was lower with PBT than PhT (79±92 vs 829±1121 cGy, respectively [P<.001]). No significant changes in LVEF or GLS for PBT or PhT were seen. Comprehensive strain analysis showed changes in endocardial longitudinal, radial, and circumferential early diastolic strain rate (SRe) in patients undergoing photon beam (PhT) up to one year of follow up (Table 1). No changes were detected in the PBT group. All other variables were non-significant (Not shown). Conclusion: This is the first longitudinal study, with a one-year follow-up, that shows the relaxation properties of LV are compromised during PhT but not PBT. These findings should be followed in time to evaluate their influence on overall heart function. Funding Acknowledgement: Type of funding sources: None.